Weather, terrain and warfare: Coalition fatalities in Afghanistan. (July 2013) - Carter, Timothy Allen; Veale, Daniel Jay
The study of conflict increasingly focuses on events and relationships within wars. Among these is the relationship between physical geography and violence. Careful examinations of the relationship between physical geography, especially weather, and events within wars are, however, still few. With increasingly available data on the violence within wars and the physical geography within states, the opportunities for such quantitative analysis have grown. In particular, the ongoing war in Afghanistan provides a useful opportunity to examine this relationship. Using this conflict, we test an argument about how the constraints and opportunities provided by physical geography, in particular daily and seasonal measures of weather, explain combat fatalities. We evaluate our argument with a series of event count models and find consistently significant evidence connecting warm temperatures, decreased visibility and windy conditions to coalition combat fatalities. Alternatively, we find mixed support that the more commonly studied elements of physical geography, distance and rough terrain are connected to these fatalities.